Györgyi Nyikos: Sustainable financing and development: Strategy and regulation: transition to sustainablefinancing models - Siklósi, Veronika (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
The topic of Györgyi Nyikos’ book is very relevant today. In recent years, leading representatives of the professional literature have increasingly focused on the concept of sustainable financing, and sustainability efforts have become increasingly important in practice, including in the Hungarian financial market. According to Milton Friedman, managers’ investment and strategic thinking was primarily driven by wealth maximization (Friedman, 1970), but in recent decades, the green perspective has become increasingly prevalent in various areas of the economy, and the transformation among financial institutions has been significant. The author provides readers with an overview of the literature on sustainable finance and the regulatory background, as promised in the title of the book, and describes the concept of sustainable finance in the Hungarian context. The author provides the reader with an overview of the literature on sustainable finance and the regulatory background, as promised in the title of the book, describes sustainability efforts, and provides guidance on the transition to green models in the financial sector.